Landscape-Scale Effects of Fire, Cats, and Feral Livestock on Threatened Savanna Mammals: Unburnt Habitat Matters More Than Pyrodiversity - Radford, Ian J.; Corey, Ben; Carnes, Karin; Shedley, Erica; McCaw, Lachie; Woolley, Leigh-Ann (Frontiers in Ecology and Evolution, 2021)
Northern Australia has undergone significant declines among threatened small and medium-sized mammals in recent decades. Conceptual models postulate that predation by feral cats is the primary driver, with changed disturbance regimes from fire and feral livestock in recent decades reducing habitat cover and exacerbating declines. However, there is little guidance on what scale habitat and disturbance attributes are most important for threatened mammals, and what elements and scale of fire mosaics actually support mammals. In this study, we test a series of hypotheses regarding the influence of site-scale (50 x 50 m) habitat and disturbance attributes, as well as local-scale (1 km radius), meta-local scale (3 km), landscape-scale (5 km) and meta-landscape scale (10 km) fire mosaic attributes on mammal abundance and richness. We found that habitat cover (rock, perennial grass and shrub cover) at the site-scale had a positive effect, and disturbance factors (feral cats, fire, feral livestock), had a negative influence on mammal abundance and richness. Models supported site-scale habitat and disturbance factors as more important for mammals than broader-scale (local up to meta-landscape scale) fire mosaic attributes. Finally, we found that increasing the extent of ≥ 4 year unburnt habitat, and having an intermediate percentage (ca. 25 %) of recently burnt (1-year burnt) habitat within the mosaic, were the most important functional elements of the fire mosaic at broad scales for mammals. Contrary to expectations, diversity of post-fire ages (‘pyrodiversity’) was negatively associated with mammal abundance and richness. These results highlight the need for management to promote retention of longer unburnt vegetation in sufficient patches across savanna landscapes (particularly of shrub and fruiting trees), maintain low-intensity patchy fire regimes, reduce the extent of intense late dry season wildfires, and to reduce the impact of feral livestock. This study provides further evidence for the role of feral cats in northern Australian mammal declines, and highlights the need for increased research into the efficacy of cat control methodologies in reducing biodiversity impacts in these extensive landscapes.